Effect of a sports beverage (Gatorade®) on roots of guinea pigs a scanning electron microscopy study - Gorjidooz, Farhard
Gatorade® is a sport beverage that is consumed world wide and is based on oral rehydration therapy. It is popularly consumed by athletes to compensate for water and electrolysis loss. The present study examined the effects of (Gatorade®) on the roots of Guinea pigs. Fifteen adult male Guinea pigs were randomly selected and divided into three equal groups. The control group, low dose group and high dose group were observed for 28 days starting from the day the orthodontic appliance was installed. The appliance used in this study consisted of 0.014 stainless steel with two arms and a helix. Gatorade® was given in adequate doses to the low dose and high dose groups. The animals were sacrificed and upper left central incisors were extracted under general anesthesia. Scanning electron microscopy was used to visualize the roots and the Image-Pro Premier software was used to measure areas of root resorption on middle of distal side of the root. The results of the study showed a significant difference between the 3 groups, with the control group showing minimum resorption followed by low dose group and finally the high dose group showing maximum root resorption. These findings suggest that (Gatorade®) could increase lthe rate of root surface resorption in Guinea pigs.